(untitled) (Balthazar, 2022)
This article intends to present the main notions of the theory of the Umwelt and the architecture of the new biology that the estonian-german biologist Jakob von Uexküll built in the first half of the 20th century. It will be shown how these concepts open up a new consideration of non-human animals, no longer as machine-objects, but as subjects in their own terms. Likewise, the reading carried out by Merleau-Ponty on von Uexküll in La Nature: Notes Cours du Collège de France and the influence that the Estonian-German had on the french philosopher will be exposed, in order to find meeting points that build bridges between the animal world and the human world.